Embedded carbon nanotubes on surface of thermoplastic poly(ether ether ketone). (4th June 2021) - Pillet, Guillaume; Puech, Pascal; Moyano, Sébastien; Neumayer, Frédéric; Bacsa, Wolfgang
Abstract: The conductivity of thermoplastic polymers can be effectively enhanced by using conductive fillers on surfaces. Carbon nanotubes are incorporated in thermoplastic poly(ether ether ketone) polymer, a polymer that is used extensively in aerospace applications, by annealing of uniform carbon nanotubes thin films on the polymer surface. Multiwall carbon nanotubes thin films of 2 cm 2 area was obtained by nanotube suspensions in methanol placed on water surface and then transferred on polymer surface. Single and multiple layers of nanotubes were deposited. The 200 nm thick composite layers so formed, showed an electrical conductivity up to 8 S/cm. Strong variations in the electronic transport was observed at 2.8 vol% of carbon nanotubes. The distribution of individual carbon nanotubes in the composite layer was studied by transmission electron microscopy. The amount of carbon nanotubes in the surface composite falling in the range of 2–12 vol% were determined through optical transmission measurements. Graphical abstract: Image 1 Highlights: Simple method in incorporating carbon nanotubes in surface of PEEK, forming a surface composite. Surface of 2 cm 2 were fabricated by transferring CNT films from water surface. The composite layer is uniform and 200–4 nm thick. The measured electrical conductivity is 5–8 S/cm at 6–12 vol% of carbon nanotubes. Carbon nanotube content was measured through optical transmission measurements.